Antagonism of local isolates of Trichoderma spp. on citrus root rot disease by Fusarium solani in the mekong delta of vietnam - Duong Minh; Jozef Coosemans; Le Lam Cuong; Ester Vandersmissen; Pham Van Kim (浙江大学学报. 农业与生命科学版)
The local isolates of Trichoderma spp. and Fusarium solani were colected from citrus orchards in the Mekong delta of Vietnam and isolated on PDA, PDB and TSM medium for antagonism and Koch's postulate testing. The results showed that the high chitinolytic enzymes content of Trichoderma isolates can antagonise with Fusarium solani isolates by preventing the germination of Fusarium macroconidia in in-vitro condition. There are five promising isolates of Trichoderma spp. having high antagonism with Fusarium solani. These Trichoderma isolates also grew well in rice straws, maize stems, weeds and water hyacinth biowaste materials. These results supply the promising trend for biological control of root rot disease on citrus orchards of the Mekong delta.